NEUSTON DIVERSITY AND DENSITY AS BIOINDICATOR FOR WATER QUALITY - Imam Safir Alwan Nurza; Jesslyn Gitta Vania; Muhammad Khatami Reynaldi; Zaki Gunawan Rasyid; Ratna Komala (BIOTROPIA, 2022)
Lakes and waterfalls are freshwater ecosystems having important roles in ecology, tourism and economic aspects.  Among living organisms existing in lakes and waterfalls is neuston.  Neuston lives on the surface and below the surface of the waters.  Neuston can be used as a bioindicator for water quality due to the neuston’s high level of sensitivity toward pollutants. The purpose of this study was to determine the density and diversity of neuston as a bioindicator for water quality in the lake and waterfall. The methods used were survey and observation. The study was carried out by using purposive sampling at two locations, namely the lake and waterfall of Situ Gunung, Sukabumi, with a sampling area of    1 x 1 m2. The samples obtained were put into bottles containing 70% alcohol to be identified in the laboratory. Environmental parameters measured were air and water temperature, water pH, water depth, turbidity, water flow velocity, dissolved oxygen, substrate and weather conditions. The results obtained indicated that the lake and waterfall of Situ Gunung, Sukabumi had highest neuston densities were shown by Gerris lacustris and Dineutus assimilis. The lowest neuston densities were shown by Metrobates hesperius, Gerris comatus, Aquarius remiges and Trepobates pictus. This study showed that the environmental parameters of the lake and waterfall of Situ Gunung, Sukabumi can still support the survival of the existing neustons.